Characteristics of the upper-level outflow and its impact on the rapid intensification of Typhoon Roke (2011) - Jin, Ru; Li, Yan; Chen, Xianyan; Li, Meiying (Frontiers in Earth Science, 2023)
In this study, we investigate the structural characteristics of the upper-level outflow and its impact on the rapid intensification (RI) of Typhoon Roke (2011), which experienced an evident outflow transformation from equatorward to poleward during its RI period. The simulations by the Weather Research and Forecasting Model suggest that the upper-level outflow extends from 100 hPa to 150 hPa, with an upper-level warm core at around 150 hPa. The upper-level outflow is enhanced ahead of the typhoon intensification, which is closely related to the outflow-environment interaction. Further analyses indicate that at the early stage of Roke (2011) before the RI, the strong equatorward outflow and the updraft south of the typhoon center are enhanced, favoring the onset of RI. During the RI period, the strong divergent flow near the entrance of the southwesterly jet in front of the upper-level trough, induces the poleward outflow. The eddy flux convergence of angular momentum inward propagated to the typhoon center from a 1000-km radius further enhances the poleward outflow and leads to the development of the vertical motion north of the typhoon center. Then Roke (2011) intensifies rapidly. Simultaneously, the shallow weak positive potential vorticity (PV) anomaly south of the southwesterly jet increases the inner-core PV, favoring the sustained intensification of Roke (2011). After Roke (2011) reaches its peak intensity, its intensity decreases due to the increase of vertical wind shear and the approaching of the southwesterly jet. It is indicated that the interaction between the upper-level outflow and the upper-tropospheric trough has significant influence on the RI of TC.